2002
DOI: 10.2202/0027-6014.1187
|View full text |Cite
|
Sign up to set email alerts
|

Student and Faculty Perceptions of Behaviors that Constitute Cheating

Abstract: This research assesses whether faculty members and students consider specific behaviors cheating, and why or why not. This study differs from previous research in that it allows students and faculty to indicate conditions that may influence their opinions regarding the integrity of academic practices. It is imperative that faculty members, advisors, counselors, and staff involved in new student orientation address academic honesty issues with students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Although most people agree on a few clear-cut situations (stealing a paper from a friend, fabricating research results, buying a paper from the Internet and submitting it as your own), gray areas and disagreement in perception exist not only between faculty and students but also among groups of faculty and groups of students. Different groups attribute varying degrees of seriousness to certain actions, such as submitting the same paper for two classes, referencing an article without having read it, paraphrasing words without attribution, or collaborating inappropriately (Higbee & Thomas, 2002).…”
Section: Limitations Of Current Approaches and Need For New Onesmentioning
confidence: 99%
“…Although most people agree on a few clear-cut situations (stealing a paper from a friend, fabricating research results, buying a paper from the Internet and submitting it as your own), gray areas and disagreement in perception exist not only between faculty and students but also among groups of faculty and groups of students. Different groups attribute varying degrees of seriousness to certain actions, such as submitting the same paper for two classes, referencing an article without having read it, paraphrasing words without attribution, or collaborating inappropriately (Higbee & Thomas, 2002).…”
Section: Limitations Of Current Approaches and Need For New Onesmentioning
confidence: 99%
“…There was also disagreement about using an old test to study without the teacher's knowledge or submitting a paper for more than one class. Exploring the more ambiguous behaviors, Higbee and Thomas (2002) surveyed students and faculty and found that student and faculty views are similar but there is considerable disagreement within each group. Burrus, McGoldrick, and Schuhmann (2007) showed that providing a definition of cheating increases the number of incidents self-reported by students.…”
mentioning
confidence: 99%
“…In addition, Higbee and Thomas (2002) questioned instructors regarding the appropriateness of a student submitting the same written assignment for more than one course. Slightly less than 50% of the faculty considered multiple submissions to be a form of academic dishonesty, 25% did not perceive it as academically dishonest, and the remaining faculty responded that their classification of the behavior would depend upon certain factors including whether the student had secured the instructor's permission (15%) and whether the essay actually met the requirements for both courses (7%).…”
Section: Conceptualizing Academic Dishonestymentioning
confidence: 99%
“…Certainly, there are behaviors that are indubitably considered dishonest (i.e., copying from another student's exams, purchasing papers, and stealing exams); nevertheless, the appropriateness of other behaviors less commonly perceived as unethical (i.e., submitting one writing assignment for more than one course or collaborating on an assignment without permission) remain troublesome for some faculty (Bennett et al, 2011;Higbee & Thomas, 2002). This is important as there are neither institutional nor industry standards on what student self-plagiarism, double-dipping, or recycling entails.…”
Section: Limitations and Recommendations For Future Researchmentioning
confidence: 99%